Going through a crisis: Firm development and firm size distributions - Christian Cordes; Tong-Yaa Su; Pontus Strimling (Philipps-University Marburg, Department of Geography, 2015)
This paper relates firm-level processes and size distributions of firms at the industry level. An analytically tractable model explores how firm growth, exit, and spinoff activity in combination with systematically appearing growth crises in organizational development translate into specific steady-state firm size distributions (FSDs). Based on anthropological, social-psychological, and economic evidence on the effects of increasing group size on performance, the model features a critical organizational size that triggers these growth crises. Together, these processes generate empirically observable size distributions of firms including right-skewed and Pareto distributions as well as self-reinforcing spinoff processes that affect an industry's FSD.
Keywords: L11; D21; C61; 330; Firm Size Distributions; Firm Growth; Critical Firm Size; Industry Evolution